Evaluasi Kinerja Perusahaan Minyak Kelapa Sawit PT. Astra Argo Lestari Tbk. (AALI) dan PT. PP London Sumatra Indonesia Tbk (LSIP) - Wendra Hartono (EXERO : Journal of Research in Business and Economics, 2019)
The movement of share prices in palm oil plantation companies is very interesting to review as an object of research. This is caused by the fluctuation of supply and demand which causes prices to soar high or fall within a period of approximately 60% in less than 2 years. This research will discuss the performance of oil palm companies using three analytical approaches such as fundamental, technical and internal and external facts that can affect the company's performance in making decisions and financial statements. This study aims to evaluate the performance of LSIP and AALI shares since 2017- Semester 1 2019 and provide consideration for potential investors before deciding to buy LSIP or AALI shares. The technique used is purposive sampling with a descriptive qualitative method approach. The results of this study are the two oil palm plantation shares are still experiencing pressure due to declining market demand and the eroded world CPO prices. This will have an impact on financial statements, especially on profitability ratios. The author recommends buying AALI stock compared to LSIP for a long period of time.